2014
DOI: 10.1371/journal.pone.0087270
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Interaction with Phospholipid Vesicles – A New Method to Accurately Determine Accessory Gene Regulator (agr) Activity

Abstract: The staphylococcal accessory gene regulatory (agr) operon is a well-characterised global regulatory element that is important in the control of virulence gene expression for Staphylococcus aureus, a major human pathogen. Hence, accurate and sensitive measurement of Agr activity is central in understanding the virulence potential of Staphylococcus aureus, especially in the context of Agr dysfunction, which has been linked with persistent bacteraemia and reduced susceptibility to glycopeptide antibiotics. Agr fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 63 publications
4
48
0
Order By: Relevance
“…It is important to define the molecular basis of agr-defective strains since the absence of haemolysis may not be sufficiently sensitive to determine Agr activity. Recent work has shown that many clinical isolates defined as nonhaemolytic on blood agar plates were capable of lysing synthetic lipid microvesicles [98]. This raises the possibility that some strains categorised as agr-defective may still express sufficient cytolytic toxin to lyse neutrophils [98].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to define the molecular basis of agr-defective strains since the absence of haemolysis may not be sufficiently sensitive to determine Agr activity. Recent work has shown that many clinical isolates defined as nonhaemolytic on blood agar plates were capable of lysing synthetic lipid microvesicles [98]. This raises the possibility that some strains categorised as agr-defective may still express sufficient cytolytic toxin to lyse neutrophils [98].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tools and techniques available for the study and examination of biofilms at early stages have been developed for fundamental laboratory research, and are not suitable or feasible for adaptation to clinical use 16,17,18 In contrast, the direct detection of cytotoxins or other virulence factors in wounds may constitute a valuable clinical indicator of CCT or early biofilm formation, and enhance clinical decision making. Because many bacterial species (including those most commonly associated with wound infections) regulate virulence factor expression based on population density, 19,20,21 the CCT and biofilm formation is likely to be marked by activation or increase in expression of virulence factors, such as cytotoxins, by predominant wound pathogens. Direct detection of virulence factors would have important advantages in this application over traditional methods for wound microbiology, which rely on cultivation and assessment of bacterial cell numbers.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus (MRSA 252) was also used for the initial assessment of mixed‐species biofilm models. All clinical strains used in this study are listed in Table . Bacteria were individually cultured from a single colony in 10 mL of broth in a shaker incubator for 18 h at 37°C, resulting in 10 9 CFU mL −1 in a final culture.…”
Section: Methodsmentioning
confidence: 99%
“…Many bacteria achieve the mutual benefits in biofilms, from sharing of resources to avoidance of host immune clearance and a better protection against the environmental threats such as antibiotics/antimicrobials. As bacteria grow into a biofilm, the changes in gene expression and regulation often results in increased pathogenicity and overall virulence activity of biofilm, and increased antimicrobial resistance compared with free floating planktonic cells . Device related infections involving multi‐species biofilm are more persistent: it becomes critical to understand and identify the factors associated with the formation of mixed‐species biofilms and their enhanced pathogenicity over the infected hosts …”
Section: Introductionmentioning
confidence: 99%